(untitled) (Indian Journal of Animal Production and Management, 2026)
The study had been conducted to investigate the use of pleutotus eryngii L. Spawn that had been grown on the wheat bran to improve it’s value with its partial replacement in stead of the yellow corn in the broiler diets with it’s effect on the productive performance of the broilers.The experiment had been Carried out by two stages, the first one was laboratorial in which the spawn had been grown on the wheat bran, then the treated wheat bran by the spawn had been dried and all the chemical analyzes had been performed on it in order to evaluate its feed value.The second stage of the experiment had been carried out in the poultry farm that belongs to the Animal production Departinent. College of Agriculture, Abu-grabe during the period 1/3/2025 until 5/4/2025. A total of 160, one day old broiler chicks, ROS 308 had been used in the experiment, those chicks had heen equally alloted on four treatments) the first treatinent was a control treatment, chicks in this control treatment had been fed on a dict containing 100%, yellow corn. Meanwhile, chicks in other treatment fed on diets Substituted by the fermented wheat bran by the spawn at rates 5, 10 and 15% for the second, third ond fourth treatment respectively. Results had been revealed a significant increase (p